(3QSGdI aj GdEYQGHs
(3ChdgG (B:s
(3hHYO, aEfj fXQJ aj Yde GdYQHjI, hhbaJ Ydi ObGFbg hMbGFbg hQGLYJ cJH GdYdeGA hJUGfjage s
(3BNQgG (B:s
(3aEf ef GdfMhjjf ef Mci Cfg ef GdYQH ef ojLQi CNkG hCHkG eLQi YUG hbaG aj bdH dGe GdaYd efgeG CdaG dJMQcgG hGfaJGM eG bHdgG hGdMeO ddg Ydi GdJeGe s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B129 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdCMeOjI HGdehUd (B(125) s
Keywords: (3GdfMhs